Potential Development of Digital Environmental Surveillance System in Dengue Control: A Qualitative Study - Purnama, Sang; Susanna, Dewi; Achmadi, Umar Fachmi; Krianto, Tri; Eryando, Tris (Open Access Macedonian Journal of Medical Sciences, 2021)
Background: The development of digital environmental technology can be conducted to implement reports, surveillance, and manage dengue control. Therefore, this study aims to determine the barriers to the use of paper-based and the potential development of digital environmental technology in dengue control. Methods In-depth qualitative interviews were conducted using 14 key informants and four focus group discussions (FGD) from May-August 2021 in Denpasar City, Bali. The interviews were consistent with the flow of the epidemiological and entomological surveillance system, the obstacles to the dengue control program, the potential for the application of digital technology, and the challenges in the application of digital surveillance technology. Furthermore, open-ended questions and content analysis by qualitative study procedures were adopted. The results were transcribed verbatim and triangulation of sources was conducted for data validation. Results The reporting system that used paper-based was not optimally implemented due to repetition of reporting, speed of information, data bias, performance measurement as well as case surveillance and reporting system constraints. An integrated digital environmental surveillance system (SILIRA) was also developed for dengue control. In the current Covid-19 pandemic, the need for digital applications is high due to the policy of not accepting guests and keeping a distance. Epidemiological surveillance for case data collection, entomological surveillance for larva density, case reporting, and educational videos are the required data in the application. Conclusion The development of an integrated application for an environmental monitoring system can be created for the continuous reporting of case information and larval density for dengue hemorrhagic fever control. Keywords: digital, surveillance, environment, dengue